An N-doped three dimensional flexible carbon/sulfur cathode for lithium sulfur battery design. Issue 8 (19th January 2016) - Mi, Liwei; Xiao, Weidong; Cui, Shizhong; Hou, Hongwei; Chen, Weihua
Abstract : Nitrogen-doped flexible carbon foam was used to fabricate a lithium sulfur battery. Abstract : Nitrogen-doped flexible carbon foam was used to fabricate a lithium sulfur battery. The stability and rate performance of the battery were evaluated. The battery with carbon foam calcined at 800 °C displayed superior stability compared with other tested batteries. Battery performance was closely related to the foam structure and component. However, good rate performance was achieved with the foam calcined at 800 °C. Cathodes with carbon foam calcined at different temperatures had diverse effects on the batteries.